Economic consequences of migraine in Sweden and implications for the cost-effectiveness of onabotulinumtoxinA (Botox) for chronic migraine in Sweden and Norway - Amanda Hansson-Hedblom; Isabelle Axelsson; Lena Jacobson; Joakim Tedroff; Fredrik Borgström (The Journal of Headache and Pain, 2020)
Abstract Background Migraine is a common and incapacitating condition, with severe impact on the quality of life (QoL) of the afflicted and their families, and negative economic consequences through decreased workforce participation, reduced functional ability and elevated healthcare costs. This study aimed to describe the economic consequences of migraine in Sweden using cost of illness survey data and, based on this data, assess the cost-effectiveness of onabotulinumtoxinA (Botox) for the treatment of chronic migraine in Sweden and Norway. Methods A survey study was conducted in Swedish migraine patients, with questions on patient characteristics, headache frequency and severity, effect on daily activities and work, QoL, health resource utilization, and medication use. Resulting costs were estimated as annual averages over subgroups of average monthly headache days. Some results were used to inform a Markov cost-effectiveness chronic migraine model. The model was adapted to Sweden and Norway using local data. The analysis perspective was semi-societal. Results’ robustness was tested using one-way, structural, and probabilistic sensitivity analyses. Results Results from the cost of illness analysis (n = 454) indicated a clear correlation between decreased QoL and increased costs with increasing monthly headache days. Total annual costs ranged from EUR 6221 in patients with 0–4 headache days per month, to EUR 57,832 in patients with 25–31. Indirect costs made up the majority of costs, ranging from 82% of total costs in the 0–4 headache days group, to 91% in 25–31 headache days. The cost-effectiveness analyses indicated that in Sweden, Botox was associated with 0.223 additional QALYs at an additional cost of EUR 4126 compared to placebo, resulting in an incremental cost-effectiveness ratio (ICER) of EUR 18,506. In Norway, Botox was associated with 0.216 additional QALYs at an additional cost of EUR 4301 compared to placebo, resulting in an ICER of EUR 19,954. Conclusions In people with migraine, an increase in monthly headache days is clearly related to lower QoL and higher costs, indicating considerable potential costs-savings in reducing the number of headache days. The main cost driver for migraine is indirect costs. Botox reduces headache days and is a cost-effective treatment for chronic migraine in Sweden and Norway.